2021
DOI: 10.1111/jonm.13343
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and its relationship with nurses' autonomy and nurse–physician collaboration in intensive care unit

Abstract: Nurses working in the intensive care unit (ICU) must take responsibility for their decisions in caring for critically ill patients (Keshk et al., 2018). The most basic tool for independent decision-making is having professional autonomy, which is more necessary for ICU nurses than nurses working in other units (Rouhi-Balasi et al., 2020). Nurses' professional autonomy is the ability to have the right and responsibility to do their job based on their patient's needs and the freedom to implement those decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
(53 reference statements)
0
28
0
2
Order By: Relevance
“…One stressor that most people face is workplace stress, which is called occupational stress [4] . Occupational stress is defined as a psycho-physical reaction that occurs when job demands exceed a person's ability or resources to cope or over-meet their needs [5] . Occupational stress is both an emotional and a physical condition that can have devastating effects and is often caused by one’s inability to provide the needs, resources, and abilities required by an employee [6] .…”
Section: Introductionmentioning
confidence: 99%
“…One stressor that most people face is workplace stress, which is called occupational stress [4] . Occupational stress is defined as a psycho-physical reaction that occurs when job demands exceed a person's ability or resources to cope or over-meet their needs [5] . Occupational stress is both an emotional and a physical condition that can have devastating effects and is often caused by one’s inability to provide the needs, resources, and abilities required by an employee [6] .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3 , the use of the neural network to extract and identify the features of the original signal can effectively extract all kinds of information contained in the signal, but it also has certain shortcomings [ 23 ]. Since the signal sampling frequency of the original signal is usually high and the amount of signal data is large, the design requirements for the network structure are high.…”
Section: Deconstruction Methods On the Relationship Between Stress An...mentioning
confidence: 99%
“…The median score for overall professional commitment in NGNs was 75 (69-86), which was accepted at a high level since the highest score on the scale 104. Similarly, NGNs had a high levels of professional commitment on the subscales of belief in goals and values, willingness to show effort, and maintaining professional membership, with median scores 15 (13)(14)(15)(16)(17), 39 (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and 23 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The highest scores on these subscales are 20, 52, and 32, respectively.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…In another study, Swedish NGNs who had recently graduated from interprofessional education university perceived the greater extent that their undergraduate training had prepared them to work together with other professions. 37 Also, studies in Iran 38 and Cyprus 39 showed that there was a significant positive relationship between professional experience and attitudes toward interprofessional collaboration among nurses. As a result, the different levels of attitudes towards interprofessional collaboration may be related to educational backgrounds, professional experiences and working environment characteristics of NGNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation